Respostas morfogênicas e estruturais de gramíneas tropicais em regime de corte no Nordeste do Brasil - Luna, Alano Albuquerque (2012)
The production of forage grasses is directly related to the morphogenesis. The knowledge of the morphogenetic and structural variables of forage plants is important for determining appropriate conditions of grazing livestock to ensure efficient and sustainable. Thus the objective of this study was to evaluate morphogenetic and structural responses of three genera of grasses, Brachiaria, Panicum and Cenchrus in a cutting regime. The experimental design was randomized blocks with three replications and six treatments. After each section were evaluated for forage production, appearance and elongation rates of leaves and stem, phyllochron, final leaf length, number of living leaves, leaf lifespan, leaf senescence rate, tiller density and tiller dynamics. On forage yield the highest values were obtained in cultivars Xaraes, Piata and Massai. The tiller density was higher for cv Massai. It is concluded that the cultivars of Panicum and Brachiaria had a higher tillering dynamics in increasing the turnover rate of tissues that are indicators of forage production, assuming that the cultivars of these genera are predisposed to use forage in the Northeast